Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$\frac{\sin A}{\sec A+\tan A-1}+ \frac{\cos A}{\csc A+\cot A-1}=1$$

Prove that L.H.S.$=$R.H.S.

This type of questions always creates problem when in right hand side some trigonometry function is given then it is bit easy to think how to proceed further.

Can some one help me not only to solve the problem but also how to tackle this type of other problem (when R.H.S. is $1$)?

share|cite|improve this question
First try converting everything into $\sin$ and $\cos$, and then try to simplify! – user46944 Jul 25 '14 at 15:04
up vote 0 down vote accepted

$$\frac{\sin A}{\sec A+\tan A-1}+ \frac{\cos A}{\csc A+\cot A-1}= \frac{\sin A}{\frac{1}{\cos A}+\frac{\sin A}{\cos A}-\frac{\cos A}{\cos A}}+ \frac{\cos A}{\frac{1}{\sin A}+\frac{\cos A}{\sin A}-\frac{\sin A}{\sin A}} =$$ $$= \frac{\sin A \cos A}{1 + \sin A - \cos A} + \frac{\sin A \cos A}{1 + \cos A - \sin A} =$$ $$= \sin A\cos A\frac{1 + \sin A - \cos A + 1 + \cos A - \sin A}{(1+\sin A - \cos A)(1 + \cos A - \sin A)} = $$ $$=\frac{2\sin A \cos A}{1 + \cos A - \sin A + \sin A + \sin A\cos A -\sin^2 A -\cos A -\cos^2 A +\sin A\cos A} = $$ $$=\frac{2\sin A \cos A}{2\sin A\cos A} = 1$$

share|cite|improve this answer

$$\frac{\sin A}{\sec A+\tan A-1}+ \frac{\cos A}{\csc A+\cot A-1}=1 $$

lets look at $$ \frac{\cos A}{\csc A+\cot A-1} = \frac{\cos A}{\sec A+1 - \tan A}\frac{1}{\cot A} = \frac{\sin A}{\sec A+1 - \tan A} $$ this leads to

$$ \frac{\sin A}{\sec A+\tan A-1}+\frac{\sin A}{\sec A+1 - \tan A} = \sin A\left[\frac{\sec A +(1-\tan A) + \sec A - (1-\tan A)}{\sec^2 A - (1-\tan A)^2}\right] = \sin A\left[\frac{2\sec A}{\sec^2 A -1-\tan ^2 A+2\tan A}\right] = \sin A\left[\frac{2\sec A }{0 + 2 \tan A}\right] = \frac{2\tan A}{2 \tan A} = 1. $$

share|cite|improve this answer

Simplify as follows : substitute $\sec \theta = \frac{1}{\cos \theta}$ and $\tan \theta = \frac{\sin \theta}{\cos \theta}$. By this, we will get first term of LHS is $\frac{\sin \theta \ \cos \theta }{1 + \sin \theta - \cos \theta }$. Similar if we substitute \second term of LHS, we will get LHS =

$\frac{\sin \theta \ \cos \theta }{1 + \sin \theta - \cos \theta }$ + $\frac{\sin \theta \ \cos \theta }{1 + \cos \theta - \sin \theta }$
$= \sin \theta \ \cos\theta [\frac {1}{1 + \sin \theta - \cos \theta} + \frac {1}{1 + \cos \theta - \sin \theta } ]$
$=\sin \theta \ \cos\theta [\frac {1}{1 + \sin \theta - \cos \theta} + \frac {1}{1 - (\sin \theta - \cos \theta) } ]$

Now simplifying $[\frac {1}{1 + \sin \theta - \cos \theta} + \frac {1}{1 - (\sin \theta - \cos \theta) } ]$ we get $\frac {1}{\cos \theta \sin \theta}$. But it is with product of $\sin \theta \cos \theta$. Hence the answer is $1$, Which is LHS. Hence proved.

And we should tackle these problems always by substituting in $\sin \theta$ and $\cos \theta$ when LHS is a number.

share|cite|improve this answer

Multiply the first fraction by $\dfrac{\cos{A}}{\cos{A}}$, and the second by $\dfrac{\sin{A}}{\sin{A}}$. We get \begin{align} LHS &=\frac{\sin A\cos A}{1+\sin A- \cos A}+\frac{\sin A\cos A}{1-(\sin A- \cos A)}\\ &=\frac{\sin A\cos A-\sin A\cos A(\sin A- \cos A)+\sin A\cos A+\sin A\cos A(\sin A- \cos A)}{1-(1-2\sin A\cos A)}\\ &=\frac{2\sin A\cos A}{2\sin A\cos A}\\ &=1\\ &=RHS \end{align}

share|cite|improve this answer

First, lets express the Pythagorean identity in another way. $$\sin^2 A +\cos^2 A = 1$$ $$\sec^2A\csc^2A(\sin^2 A +\cos^2 A) = \sec^2A\csc^2A\cdot1$$ $$\sec^2A+\csc^2 A = \sec^2A\csc^2A$$ Continuing $\dots$

$$\begin{array}{lll} \frac{\sin A}{\sec A+\tan A-1}+ \frac{\cos A}{\csc A+\cot A-1} & = & \frac{1}{\csc A(\sec A+\tan A-1)}+\frac{1}{\sec A(\csc A+\cot A-1)} \\ & = & \frac{1}{\csc A\sec A+\sec A-\csc A}+\frac{1}{\sec A\csc A+\csc A-\sec A} \\ & = & \frac{1}{\sec A\csc A+(\sec A-\csc A)}+\frac{1}{\sec A\csc A-(\sec A-\csc A)} \\ & = & \frac{\sec A\csc A\color{blue}{+(\sec A-\csc A)} + \sec A\csc A\color{blue}{-(\sec A-\csc A)}}{(\sec A\csc A+(\sec A-\csc A))(\sec A\csc A-(\sec A-\csc A))}\\ & = & \frac{2\sec A\csc A}{\sec^2A \csc^2 A-(\sec A - \csc A)^2}\\ & = & \frac{2\sec A\csc A}{\sec^2A \csc^2 A-(\color{blue}{\sec^2 A + \csc^2 A} - 2\sec A\csc A)}\\ & = & \frac{2\sec A\csc A}{\sec^2A \csc^2 A-\color{blue}{\sec^2 A\csc^2 A} + 2\sec A\csc A}\\ & = & \frac{2\sec A\csc A}{2\sec A\csc A}\\ & = & 1 \end{array}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.